Halal Lifestyle: How Does Islamic Financial Literacy and Halal Literacy Encourage It? - Guntoro, Dibyo Waskito; Sholekhah, irmadatus; Solikin, Asep (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
The global expansion of the Halal market highlights the growing adoption of a Halal Lifestyle, yet a persistent gap exists between Muslim consumers' intentions and their actual purchasing behavior. This study addresses a critical gap in halal consumption literature by examining how Islamic Financial Literacy (IFL) and Halal Literacy (HL) jointly influence Halal Lifestyle adoption. While previous research emphasizes religiosity, it overlooks the role of specific knowledge domains in bridging the "halal consciousness gap" between intention and behavior. Grounded in an integrated Theory of Islamic Planned Behavior and Behavior Reasoning Theory framework, we propose IFL and HL serve as cognitive tools that enhance perceived behavioral control and provide concrete reasons for consistent halal consumption. Using quantitative data from 108 Muslim students in Indonesia, multiple linear regression analysis reveals both IFL (β = 0.217, p = 0.021) and HL (β = 0.285, p = 0.003) significantly predict Halal Lifestyle, collectively explaining 11.2% of variance (R² = 0.112). The findings demonstrate these literacies operate as complementary mechanisms translating religious motives into cross-domain consumption practices. The study contributes theoretically by validating the integrated TIPB-BRT framework and establishing IFL as a relevant construct beyond financial contexts. Practically, it advocates shifting from product provision to building a "smart halal ecosystem" through integrated literacy campaigns, empowering consumers to make informed choices across food, finance, and lifestyle domains.